PREVALENCE OF POSTPARTUM DEPRESSION AND ITS ASSOCIATION WITH ANTENATAL DEPRESSION AMONGST WOMEN - Zaidi, Farhin; Anjum, Rubi; Nigam, Aruna (Journal of Drug Delivery and Therapeutics, 2018)
Background: A prospective cross sectional study was designed to determine the prevalence rate of postpartum depression and its association with antenatal depression among women coming to the antenatal Clinic and birthing at HAHC Centenary Hospital, New Delhi. Material & Methods: 149 women by the assistance of EPDS (Hindi version) were screened at 6 weeks of their delivery. The participants were then divided on the basis of presence and absence of depression into two groups as depressed and non-depressed women. Results: 19 out 149 postnatal women scored â‰¥ 10 on EPDS which suggest the 12.75% prevalence rate of postnatal depression. Moreover 8(42.1 %) women among 19 depressed postnatal women and 25(19.3 %) women among 130 non-depressed postnatal women were found to have depression since their time of pregnancy thus a significant association (p-value= 0.025) was obtained. Conclusion: PPD is a major health problem in our community. Moreover, presence of depression during pregnancy significantly predisposes the postnatal mothers to be a victim of PPD. Therefore an early screening of the perinatal women is needed to unreveal the hidden cases as well as to prevent the mothers from the cruel penalties of PPD. Keywords: Postpartum Depression, Screening, perinatal women, Edinburgh Postnatal Depression Scale.Â